Networking Among Southeast Asian Psychological Societies to Improve Services * - A. Supratiknya (Faculty of Psychology Universitas Gadjah Mada, 2006)
Psychology as a common sense knowledge about people and their behavior might have been familiar to every culture since the beginning of the human history. As a scientific discipline, however, it seems to be a Western invention. Some even contented that is only the product of the transition from traditional or premodern to modern Western society in the 19 th century (Sampson, 1989). This transition involves change of the functional unit of the social order from the community or any other form of social groupings to the individual. Based on a liberal individualist framework as well as a voluntarist notion of personhood, the modern Western world view the person as a self‐contained individual whose values and relations are the products of her or his own choice. Individuals are antecedent to the society in which they live and the possession of a self is given prior to its